Relationship Between Waiting Time and Patient Satisfaction at the Surgery Polyclinic of Bekasi District Hospital - Yuliati, Yuliati (STIKep PPNI Jawa Barat, 2024)
Aims : the study aimed to determine the correlation between waiting time and patient satisfaction at the Surgical Polyclinic of the Outpatient Installation at Bekasi District Hospital. Methods : Time spent waiting serves as the independent variable in this cross-sectional study, with patient satisfaction serving as the dependent variable. Forty participants were surveyed using questionnaires as the major source of information in July 2022. Results : The analysis reveals that P =.000 (P Value.05) is derived from a Chi Square test of association between waiting time factors and patient satisfaction. Patient happiness seems to correlate with how long they have to wait before being seen. Strengthen time management skills to ensure that medical care is delivered on time and with the highest possible quality. Conclusions : The research find a significant correlation between patient satisfaction and waiting time in the Surgical Polyclinic at Bekasi District Hospital, suggesting the need for improved time discipline and more responsive medical personnel.